2023
DOI: 10.3390/plants12152874
|View full text |Cite
|
Sign up to set email alerts
|

Genebanks at Risk: Hazard Assessment and Risk Management of National and International Genebanks

Theresa Herbold,
Johannes M. M. Engels

Abstract: Genebanks are crucial for safeguarding global crop diversity but are themselves exposed to several risks. However, a scientific basis for identifying, assessing, and managing risks is still lacking. Addressing these research gaps, this study provides risk analysis for three key risk groups: natural hazards, political risks, and financial risks, carried out on a sample of 80 important national and international genebanks, comprising at least 4.78 million accessions or roughly 65% of the reported total of ex sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…With the encouragement of the FAO Commission on Genetic Resources for Food and Agriculture to establish genebanks for the storage of collected genetic resources and with technical guidance and assistance from the IBPGR, almost 2000 genebanks have been established worldwide since the middle of the last century. Because plant genetic resources, genebanks, and the genetic resources they contain can be threatened, Herbold and Engels [ 14 ] analysed the different types of risks that undermine the safety and security of the genebanks and their collections and suggested remedies for how such risks can be reduced. Another critical aspect of the efficiency and effectiveness of genebanks is the assessment of their quality performance.…”
Section: Highlights Of the Papers Published In This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…With the encouragement of the FAO Commission on Genetic Resources for Food and Agriculture to establish genebanks for the storage of collected genetic resources and with technical guidance and assistance from the IBPGR, almost 2000 genebanks have been established worldwide since the middle of the last century. Because plant genetic resources, genebanks, and the genetic resources they contain can be threatened, Herbold and Engels [ 14 ] analysed the different types of risks that undermine the safety and security of the genebanks and their collections and suggested remedies for how such risks can be reduced. Another critical aspect of the efficiency and effectiveness of genebanks is the assessment of their quality performance.…”
Section: Highlights Of the Papers Published In This Special Issuementioning
confidence: 99%
“…Apart from the threat to genetic resources in nature and/or farmers’ fields as well as in genebanks, genebanks themselves are exposed to a series of risks that may originate from natural hazards, such as earthquakes and storms, but also from political or financial issues. Herbold and Engels [ 14 ] undertook risk analyses of 80 important national and international genebanks regarding natural hazards and political and financial risks, and they concluded that there are large differences in the risk exposure of genebanks, making a location- and institution-specific risk assessment indispensable. Such risk assessments would help create more awareness at the local or national (political) level, hopefully resulting in the implementation of measures that mitigate the impact of risks, both for the genebank structures as well as for the safety of the collections.…”
Section: Key Messagesmentioning
confidence: 99%
“…First, genebanks' storage space, budgets, and staff expertise are frequently limited. Continuously increasing the germplasm collection by incorporating the new accession may strain these resources and risk the overall effectiveness of genebank activities [6]. Second, an overabundance of the collection may degrade its representativeness.…”
Section: Introductionmentioning
confidence: 99%